2010
DOI: 10.1002/jcb.22898
|View full text |Cite|
|
Sign up to set email alerts
|

Different apoptotic effects of wogonin via induction of H2O2 generation and Ca2+ overload in malignant hepatoma and normal hepatic cells

Abstract: Wogonin, a major active constituent of Scutellaria baicalensis, possesses potent anticancer activities both in vivo and in vitro. This paper describes the different apoptotic effects of wogonin in HepG2 and L02 cells and the possible mechanism for the differences. Through DAPI staining, Annexin-V/PI double-staining assay, JC-1 detection and the expressions of the key apoptotic proteins, we find that wogonin prefers to induce apoptosis in HepG2 cells through the mitochondrial pathway, while has much less effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…33,34 As a type of critical target cell line for the study of liver cancer therapy, HepG2 has been investigated by many researchers. 35,36 How SWNHs affect the biological functions of human hepatoma cell lines such as HepG2 or normal liver cell lines such as L02 was unknown, and there were no reports on the differences in roles and mechanisms between the material and the normal or cancer cells. To address these…”
Section: Introductionmentioning
confidence: 99%
“…33,34 As a type of critical target cell line for the study of liver cancer therapy, HepG2 has been investigated by many researchers. 35,36 How SWNHs affect the biological functions of human hepatoma cell lines such as HepG2 or normal liver cell lines such as L02 was unknown, and there were no reports on the differences in roles and mechanisms between the material and the normal or cancer cells. To address these…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has shown that CaMKII activation is closely related to increased intracellular calcium levels [8, 9]. In addition, PLCγ1 signaling has also been proven to facilitate the influx of intracellular Ca 2+ [14, 15]. Thus, PLCγ1 may be located upstream of CaMKII by influencing intracellular calcium levels in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we demonstrated that PLCγ1, known as an important serine threonine kinase of PLC, is activated in response to periodic mechanical stress [13]. Increasing evidence suggests that PLCγ1 activation elevates the levels of cytosolic Ca 2+ by increasing calcium release from the endoplasmic reticulum [14, 15]. Thus, we have reason to speculate that in chondrocytes, periodic mechanical stress-induced PLCγ1 activation would induce the influx of intracellular Ca 2+ that is responsible for the activation of CaMKII.…”
Section: Introductionmentioning
confidence: 99%
“…A number of flavonoids were shown to have both pro-and antioxidant effects on cancer cells, by ϭϳ their ability to deplete glutathione (GSH) of tumor cells (Li-Weber, 2009). Moreover, wogonin was shown to deoxidize .O-to H 2 O 2 via the antiradical enzyme SOD, shifting the redox balance of reactive oxygen species to a more reductive state and heightened the total reactive oxygen species levels (Wei et al, 2010). Therefore it is believed that the anticancer activity of flavonoids may also involve a pro-oxidant mechanism.…”
Section: Discussionmentioning
confidence: 99%